Addressing human behavior in conservation design: Learning from program applications. (March 2023) - Sullivan-Wiley, Kira A.; Shyamsundar, Priya; Musengezi, Jessica
Abstract: Human behavior plays a key role in determining conservation outcomes. The actions of multi-national environmental non-government organizations (NGOs) offer a way to critically assess behavior change approaches across geographies and conservation targets. In this paper, we seek to understand the range of ways in which practitioners in one such organization conceptualize and integrate human behavior into their conservation programs. This paper uses a survey of the NGO's interventions ( n = 161) to identify several case studies, three of which we present here to illustrate how human behavior considerations were addressed in different contexts across the globe. The first case focuses on political support for water quality legislation in Long Island, USA, the second on women's engagement in eco-entrepreneurship in Oceania, and the third on fishing and agricultural practice in communities near Mahale Mountain National Park, Tanzania. Using the lens of applied work across varied contexts offers high-level insights on (1) the array of behavioral goals and strategies currently used in conservation interventions; (2) challenges facing project managers in using behavioral insights; and (3) areas of opportunity for improving and scaling up the use of behavioral insights in conservation. Our results indicate that many conservation interventions would benefit from reconceptualizing traditional environmental goals into social-environmental goals, framing work in the context of both environmental and behavioral outcomes, questioning and verifying behavioral assumptions, and tracking behavioral outcomes in project monitoring, reporting, and evaluation. Highlights: Behavior centered design is gaining momentum in conservation. Case studies illustrate how different programs apply behavioral insights in conservation. Behavioral strategies are usually used in combination and complement other strategies. Behavioral assumptions, goals and targets need enhanced monitoring and evaluation.